PENGARUH INTELLECTUAL CAPITAL TERHADAP RETURN ON ASSETS (ROA) PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Herlina Herlina; Siti Mudawanah; Ahmad Febru Yulyana (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2022)
This research aims to determine the influence of Intellectual Capital which consists of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) on the Return on Assets (ROA) of Food and Beverage Companies listed on the Stock Exchange Indonesia.The population of this research is food and beverage companies that are consistently listed on the Indonesia Stock Exchange during the 2014-2017 period, totaling 18 companies. The sampling technique used was purposive sampling technique. Based on the established criteria obtained a sample of 10 companies. The type of data used is secondary data taken by the documentation method by accessing the site idx.co.id, Sahamok.com, and the official website of each company. The data analysis technique used is multiple regression analysis. The results of this research show that : (1) there is a significant effect between Value Added Capital Employed (VACA) on Return On Assets, with a correlation coefficient of 0.498, and a significant value of 0.009 0.05; (2) there is no significant effect between Value Added Human Capital (VAHU) on Return On Assets, with a correlation coefficient of 0.071 and a significant value of 0.502 0.05; (3) there is a significant influence between Structural Capital Value Added (STVA) on Return On Assets, with a correlation coefficient of 0,000, and a significant value of 0,000 0,05; (4) there is a significant influence between Value Added Capital Employed (VACA), Value Added Human Capital (VAHU) and Structural Capital Value Added (STVA) together on Return On Assets, with the R square determination coefficient generated at 64.7 % and significant value 0,000 0,05 and value F count 22,017 Ftable 2.63.